Why do participants in voluntary organizations leave? Exploring the relationship between value congruence and length of stay. Issue 3 (11th September 2020) - Ihm, Jennifer; Baek, Young Min
Abstract: Recognizing the importance of values and the specific characteristics of participants and situations in voluntary organizations, we examine how value congruence—the fit or compatibility of values between participants and the organization, or among participants—interacts with personal and situational factors to predict participants' length of stay in their organizations. Introducing the case of a voluntary organization that offers shared housing, we measure value congruence through textual similarity in the self‐introduction documents of 49 participants and the organization's mission statement. This approach differs from the self‐reported measures based on participants' perceptions or recalled interactions used in previous studies. In line with expectation‐disconfirmation theory, participants with the strongest beliefs in organizational values had shorter lengths of stay. The amount of intraorganizational communication also moderated the relationship between value congruence and length of stay. This study provides theoretical and methodological implications for nonprofit management by considering personal and situational factors and evaluating value congruence by textual similarity.